Anticoagulant therapy in head injury‐associated cerebral sinovenous thrombosis in children. Issue 11 (11th August 2014) - Xavier, Frederico; Komvilaisak, Patcharee; Williams, Suzan; Kulkarni, Abhaya V.; deVeber, Gabrielle; Moharir, Mahendranath D.
Abstract Background Head injury is a risk factor for cerebral sinovenous thrombosis (CSVT) in children. Literature concerning head injury‐associated CSVT (HIA‐CSVT) is scarce. Data supporting safety and efficacy of anticoagulant therapy (ACT) in childhood CSVT is emerging. However, intracranial hemorrhage (ICH) occurs frequently in children with HIA‐CSVT at diagnosis making initiation of ACT controversial due to the fear of worsening of ICH. Procedure We conducted a retrospective descriptive review of a consecutive cohort of children with HIA‐CSVT from 1998 to 2012. Results Twenty patients (14 males, mean age 7 years) with HIA‐CSVT were identified. Most (19/20 [95%]) had significant ICH at diagnosis. None received ACT at diagnosis. Fourteen (70%) were later (median 7 days post‐trauma, range 2–48 days) treated with ACT due to CSVT persistence (nine) and propagation (five), despite ICH in 13. None of the treated patients, including the 13 with pre‐existing ICH, had significant worsening of hemorrhage. Three (21%) treated patients had minor asymptomatic extension of their hemorrhage and further ACT was withheld. No patient died while on ACT. No patient experienced CSVT propagation on ACT. Clinical outcomes were normal (no neurologic deficits) in 5/20(25%), mild neurological deficits in 10/20(50%), and moderate‐severe neurological deficits in 5/20(25%). Small sample size did not permit assessment of the effect of ACT on outcome. Conclusions Anticoagulant therapy is safe in selected children with HIA‐CSVT. ICH is not an absolute contraindication to ACT in children with HIA‐CSVT. Pediatr Blood Cancer 2014;61:2037–2042. © 2014 Wiley Periodicals, Inc.